Genomic analysis of antibiotic resistance for Acinetobacter baumannii in a critical care center. Issue 1 (22nd July 2019) - Murata, Kensuke; Inoue, Yoshiaki; Kaiho, Mayuko; Nakazawa, Takeshi; Sasaki, Shin‐ichi; Miyake, Kazunori; Matsuda, Shigeru; Tanaka, Hiroshi
Abstract : Aim: Acinetobacter baumannii is commonly associated with outbreaks and antibiotic‐resistant nosocomial infection. This study aimed to determine the relationship between antibiotic resistance and genotypes of A. baumannii . Methods: A study was undertaken in the critical care center (CCC) of Juntendo University Urayasu Hospital (Urayasu, Japan) between January 2012 and September 2015. Antimicrobial susceptibility tests were carried out according to the Clinical and Laboratory Standards Institute guidelines. All A. baumannii isolates were verified to carry carbapenemase genes and the IS A ba1 element using polymerase chain reaction. The genetic relationship of all A. baumannii isolates was determined by pulsed‐field gel electrophoresis and multilocus sequence typing. Results: During the study period, 1634 patients were admitted to the CCC. Acinetobacter baumannii was detected in 43 patients (average age, 58 ± 19 years; 67.4% men). Six patients were determined to be extensively drug‐resistant A. baumannii and 21 patients determined to be multidrug‐resistant A. baumannii . Antimicrobial susceptibility linked genotypes of A. baumannii . Molecular characterization by pulsed‐field gel electrophoresis and multilocus sequence typing showed that closely related clones of A. baumannii had spread in the CCC. Conclusion: Resistance to antimicrobial drugs was significantly associated with certain A. baumannii genotypic types and molecular types. Thus, we might be able to predict whether the genotype has spread in the CCC or not when the susceptibility is examined, facilitating the appropriate isolation of patients. Abstract : In this retrospective study, we undertook genotypic determination of Acinetobacter baumannii isolates from patients in the critical care center between January 2012 and September 2015 by polymerase chain reaction. We also determined the genetic relationship of all A. baumannii isolates in the study using pulsed‐field gel electrophoresis and multilocus sequence typing, and evaluated their antimicrobial sensitivity/resistance patterns. Our results showed that closely related A. baumannii clones were spreading in the critical care center.